On the nature of man - Nemesios, emeský biskup, činný 4. století-5. století (Translated texts for historians ;, 2008)
Nemesius' treatise On the Nature of Man is an important text for historians of ancient thought, not only as a much-quarried source of evidence for earlier works now lost, but also as an indication of intellectual life in the late fourth century AD. The author was a Christian bishop; the subject is the nature of human beings and their place in the scheme of created things. The medical works of Galen and the philosophical writings of Plato, Aristotle and the Neoplatonist Porphyry are all major influences on Nemesius; so too the controversial Christian Origen. On the Nature of Man provides the first kown compendium of theological anthropology with a Christian orientation and considerably influenced later Byzantine and medieval Latin philosophical theology.